1989
DOI: 10.1159/000216035
|View full text |Cite
|
Sign up to set email alerts
|

Computerized Analysis of the in vitro Activation of the Plasmatic Clotting System

Abstract: We analyzed the kinetics of the clotting system by a chromogenic substrate method in plasma with isolated factor deficiency. The sigmoidal extinction curve obtained was mathematically described by an equation with four constants K(i) relating to the activity of clotting factors and to the concentration of fibrinogen. The analysis of constants obtained from dilution series of factor-deficient plasma revealed a distribution pattern differing from one factor to another both for the extrinsic and the intrinsic sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 8 publications
1
20
0
Order By: Relevance
“…transformation of fibrinogen to fibrin [7], According to these experiments, K(l) in creases whereas K(2) decreases with increas ing fibrinogen concentrations. However, the distribution of the K(2)/K(l) patterns for isolated factor deficiency remains qualita tively unchanged.…”
Section: Resultsmentioning
confidence: 64%
See 4 more Smart Citations
“…transformation of fibrinogen to fibrin [7], According to these experiments, K(l) in creases whereas K(2) decreases with increas ing fibrinogen concentrations. However, the distribution of the K(2)/K(l) patterns for isolated factor deficiency remains qualita tively unchanged.…”
Section: Resultsmentioning
confidence: 64%
“…Therefore, the equations describing the for mation of the complexes need not to be included in the model. Interactions between the extrinsic and intrinsic clotting system are ignored, since the results from the experiments indicated that the extrinsic sys tem is not significantly affected by factor VIII and factor IX deficiency [7], The feedback reaction on factor V via factor Ila and the formation of the prothrombinase complex can be introduced by equations, which describe the termolecular mechanism of action:…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations